Increased Information Flow between Hydropower Scheduling Models through Extended Cut Sharing. (January 2016) - Gjerden, Knut Skogstrand; Skjelbred, Hans Ivar; Mo, Birger
Abstract: We present initial results and description of a method for coupling long term hydro scheduling models to short term hydro schedul- ing models. The method is based on an established approach but extends on the principle to increase the available information of the future estimates provided by the long term model.